Chapter La governance dell'accoglienza straordinaria in Toscana - Cuevas, Miriam (Studi e saggi, 2021)
How was migration multilevel governance implemented at the regional level in Italy during the refugee crisis? The chapter analyses the case study of the Tuscany Region in 2017-2018. The first part focuses on the migration reception model adopted. The second part describes the distribution of asylum seekers in the provinces of Florence, Siena and Arezzo. The last part deals with a comparative analysis of the tendering procedures for CAS (Centri di accoglienza straordinari- extraordinary centers of reception) published between 2015 and 2018 by the Prefectures of Florence, Siena and Arezzo.